Otimização numérica da produção de glutationa por saccharomyces cerevisiae utilizando subprodutos industriais - Cruz, Késia de Souza (2016)
Recent studies show that often, pathologies are caused by Reactive oxygen species (ROS). The ROS are associated with the oxidative stress in the cells. The body uses the antioxidants to defend itself from the consequences of this process. An example of an antioxidant with different functions in an organism is the Glutathione (GSH). It is a cellular thiol with low molecular mass, that’s synthesized by chemical, enzymatic and fermentative methods. Since it is environmentally and economically viable, the use of the fermentative process has gained scientific visibility. The use of mathematical models is an alternative that helps in the production of Glutathione. Considering these observations, the present study's aimed to elaborate a mathematical model for production and prediction of GSH for Saccharomyces cerevisiae, as well as to validate its numerical optimization experimentally. For the mathematical model in this process, was used the Central Composite Rotational Design 2², having as an answer, the GSH and biomass values in function with the concentration of molasses and glycerol during a period of 96 hours of fermentation. Based on these results, a hybrid model was made, having as a result, the specific rate of GSH formation. The final model was adjusted to a polynomial function using the method of least squares. Experimentally, the maximum production of GSH was found to be, in 72 hours (119,6 mg L-1) using 76,9 g L-1of molasses and glycerol, respectively. Applying the model for similar conditions, it was estimated to a 118,6mg L-1. The experimental results were then statistically analyzed to verify their similarity. The numerical optimization was made by setting the clock for 72 hours. At this step, the concentration of molasses and glycerol were varied until the best conditions to produce GSH were met. The optimization helped to derive an estimate that 70 g L-1of sugar cane molasses and 40 g L-1of glycerol can guarantee the production of 126 mg L-1of GSH. Based on the accuracy of the observations, the same conditions were used as a central point for the validation of the model - Factorial Design2². The results obtained under these conditions helped establish that the central point of the proposed design for the validation of the model, is 127,3mg L-1of GSH in 72 hours. The validation of this mathematical model by the numerical optimization proved that it was effective for the production and prediction of Glutathione by Saccharomyces cerevisiae, using industrial by-products.